2019
DOI: 10.1007/s12035-019-01816-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a Acutely Regulates Synaptic Efficacy in the Adult Dentate Gyrus In Vivo

Abstract: Activity-dependent synaptic plasticity involves rapid regulation of neuronal protein synthesis on a timescale of minutes. miRNA function in synaptic plasticity and memory formation has been elucidated by stable experimental manipulation of miRNA expression and activity using transgenic approaches and viral vectors. However, the impact of rapid miRNA modulation on synaptic efficacy is unknown. Here, we examined the effect of acute (12 min), intrahippocampal infusion of a miR-34a antagonist (antimiR) on medial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…Arc is a target of the microRNA, miR34a (Wibrand et al., 2012). Local intrahippocampal infusion of a miR34a‐inhibitor (Berentsen et al, 2019) induced upregulation of Arc and several other bioinformatically predicted miR34a targets. The depression of synaptic transmission started within 10 min of infusion and was nucleotide sequence‐specific, as scrambled and mismatch antagomirs did not affect miR34a target expression or synaptic efficacy.…”
Section: Reconciling Differences In Arc Functionmentioning
confidence: 99%
“…Arc is a target of the microRNA, miR34a (Wibrand et al., 2012). Local intrahippocampal infusion of a miR34a‐inhibitor (Berentsen et al, 2019) induced upregulation of Arc and several other bioinformatically predicted miR34a targets. The depression of synaptic transmission started within 10 min of infusion and was nucleotide sequence‐specific, as scrambled and mismatch antagomirs did not affect miR34a target expression or synaptic efficacy.…”
Section: Reconciling Differences In Arc Functionmentioning
confidence: 99%
“…miR-9-derived miR-9-3p [226] Dystrophin [226]; Voltage-dependent Calcium channel, g subunit [226,227]; Leucine rich repeat transmembrane neuronal 1 [226,228]; Cadherin 2 [226,229]; Fibronectin [230]; Calcineurin B, type I [226,231] Regulates synaptic plasticity and memory [226] Found in serum exosomes of acute ischemic stroke patients [217] miR-17-92 cluster: miR-17, miR-18a, miR-19a, miR-19b, miR-20a, and miR-92a [213,[232][233][234] Phosphatase and Tensin Homolog (PTEN) [211,234] -Regulate axonal outgrowth in development [211]; -Regulate adult hippocampal neurogenesis, anxiety, and depression [232]; -Enhance neuroplasticity and functional recovery after stroke [233,234]; -Enhance neurite remodeling, neurogenesis and angiogenesis in post-stroke rats [233]; -Ablation in mouse impairs hippocampal-dependent learning and memory [212] miR-19a found in exosomes [213,233] miR-26a [209] PTEN, GSK-3, BDNF [209] Stimulates neurite/axonal elongation [209] Found in astrocytic exosomes [209] miR-29c [235] Beta secretase 1 (BACE1) [236] This microRNA can be an endogenous regulator of the BACE 1 enzyme, and thus of beta amyloid precursor protein (APP) metabolism. [236] Found in exosomes contained in frozen post-mortem prefrontal cortex from bipolar individuals [235] miR-34a [237] Activity-regulated cytoskeleton-associated protein (Arc) Chicken ovalbumin upstream promoter transcription fa...…”
Section: Synaptic Plasticity: the Possible Role Of Evs And Their Cargoesmentioning
confidence: 99%
“…In fact, the generation of LTP through the N-methyl-D-aspartate receptor (NMDAR) activates transcription factors that promote the expression of genes responsible for its maintenance (82). Indeed, it has been demonstrated that through enhanced expression of the Arc gene, a key regulator of synaptic plasticity, miR-34a regulates basal synaptic efficacy in the adult medial perforant path-evoked synaptic transmission in the DG (83).…”
Section: Microglia Morphology and Cognitive Performancesmentioning
confidence: 99%